Pandangan Alkitab tentang Gereja Sebagai Komunitas Pembelajaran dan Pembinaan Pada Masa Kini (International Forum of Researchers and Lecturers, 2025)
Social changes due to technological advancements have transformed the way people relate and associate with one another. Relationships can now be developed more easily, more affordably, and more quickly. As a community, the church is